(untitled) (The Agriculturists, 2010)
A study was conducted at the BRRI research farm during 2001 to determine the distribution of soil phosphorus (P) fractions in P-deficient rice soil that received varied amount of P as triple super phosphate (TSP) and di-ammonium phosphate (DAP). Solution P ranged from 0.06 to 0.08 mg L-1 which was significantly greater in long duration variety (LDV) compared to short duration variety (SDV) at Pcontrol conditions. The increase in NaHCO3-Pi pool was 4.5-35.2% greater with LDV compared to SDV at 30-45 kg P ha-1. There was 7-10% greater NaOH-Po after growing LDV compared to SDV at larger P doses as TSP. The buildup of NaOH-Po pool was greater by 18% after growth of SDV compared to LDV when P was added as DAP. The NaOH-Pi fraction increased by about 21-212% with P application compared to P control irrespective of P sources. The larger HCl-Pi fraction buildup (21-152%) took place because of P application either as TSP or DAP, especially with the LDV. The increase in residual-P fraction was 10-158% because of P-fertilization and rice genotypes compared to control. Under Pfertilized conditions, NaHCO3-Pi and NaOH-Po appeared to have acted as sinks of added P-fertilizer. Cultivation of rice genotypes at 30-40 kg P ha-1 under lowland situations further contributes to P buildup in soil which could be utilized in the succeeding crops for profitable farming.